0.375x*-0.33333333333333333333333333333333x+6=0.16666666666666666666666666666667x

Simple and best practice solution for 0.375x*-0.33333333333333333333333333333333x+6=0.16666666666666666666666666666667x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use i

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.375x*-0.33333333333333333333333333333333x+6=0.16666666666666666666666666666667x equation:


Simplifying
0.375x * -0.33333333333333333333333333333333x + 6 = 0.16666666666666666666666666666667x

Reorder the terms for easier multiplication:
0.375 * -0.33333333333333333333333333333333x * x + 6 = 0.16666666666666666666666666666667x

Multiply 0.375 * -0.33333333333333333333333333333333
-0.125x * x + 6 = 0.16666666666666666666666666666667x

Multiply x * x
-0.125x2 + 6 = 0.16666666666666666666666666666667x

Reorder the terms:
6 + -0.125x2 = 0.16666666666666666666666666666667x

Solving
6 + -0.125x2 = 0.16666666666666666666666666666667x

Solving for variable 'x'.

Reorder the terms:
6 + -0.16666666666666666666666666666667x + -0.125x2 = 0.16666666666666666666666666666667x + -0.16666666666666666666666666666667x

Combine like terms: 0.16666666666666666666666666666667x + -0.16666666666666666666666666666667x = 0.00000000000000000000000000000000
6 + -0.16666666666666666666666666666667x + -0.125x2 = 0.00000000000000000000000000000000

Begin completing the square.  Divide all terms by
-0.125 the coefficient of the squared term: 

Divide each side by '-0.125'.
-48 + 1.333333333x + x2 = 0.00000000000000000000000000000

Move the constant term to the right:

Add '48' to each side of the equation.
-48 + 1.333333333x + 48 + x2 = 0.00000000000000000000000000000 + 48

Reorder the terms:
-48 + 48 + 1.333333333x + x2 = 0.00000000000000000000000000000 + 48

Combine like terms: -48 + 48 = 0
0 + 1.333333333x + x2 = 0.00000000000000000000000000000 + 48
1.333333333x + x2 = 0.00000000000000000000000000000 + 48

Combine like terms: 0.00000000000000000000000000000 + 48 = 48
1.333333333x + x2 = 48

The x term is 1.333333333x.  Take half its coefficient (0.6666666665).
Square it (0.4444444442) and add it to both sides.

Add '0.4444444442' to each side of the equation.
1.333333333x + 0.4444444442 + x2 = 48 + 0.4444444442

Reorder the terms:
0.4444444442 + 1.333333333x + x2 = 48 + 0.4444444442

Combine like terms: 48 + 0.4444444442 = 48.4444444442
0.4444444442 + 1.333333333x + x2 = 48.4444444442

Factor a perfect square on the left side:
(x + 0.6666666665)(x + 0.6666666665) = 48.4444444442

Calculate the square root of the right side: 6.960204339

Break this problem into two subproblems by setting 
(x + 0.6666666665) equal to 6.960204339 and -6.960204339.

Subproblem 1

x + 0.6666666665 = 6.960204339 Simplifying x + 0.6666666665 = 6.960204339 Reorder the terms: 0.6666666665 + x = 6.960204339 Solving 0.6666666665 + x = 6.960204339 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = 6.960204339 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = 6.960204339 + -0.6666666665 x = 6.960204339 + -0.6666666665 Combine like terms: 6.960204339 + -0.6666666665 = 6.2935376725 x = 6.2935376725 Simplifying x = 6.2935376725

Subproblem 2

x + 0.6666666665 = -6.960204339 Simplifying x + 0.6666666665 = -6.960204339 Reorder the terms: 0.6666666665 + x = -6.960204339 Solving 0.6666666665 + x = -6.960204339 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = -6.960204339 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = -6.960204339 + -0.6666666665 x = -6.960204339 + -0.6666666665 Combine like terms: -6.960204339 + -0.6666666665 = -7.6268710055 x = -7.6268710055 Simplifying x = -7.6268710055

Solution

The solution to the problem is based on the solutions from the subproblems. x = {6.2935376725, -7.6268710055}

See similar equations:

| 0=y^2-240y+11000 | | -0.16666666666666666666666666666667*17+0.33333333333333333333333333333333*4=x+4 | | 2x^2-240x+5500=x | | 4x=148 | | a^2-4a+5=0 | | |10x-6|=|3x+17| | | y^2+5y-5= | | 5(y+4)=7(x-2) | | 10y-7+5y= | | -6b=54 | | 5t-22=-31+2t | | 4y-25=-27+2y | | D^2-14d+49= | | -7b+4a-6a-9b= | | 14(.3n+.31)=5.18-(.4-4.22n) | | 2t^2=27t | | -(y+2)-(13-y)= | | 81x^3=0 | | 4k+4=k^2 | | 5(2+4)=7(2-2) | | -4x+7=-9 | | 3(3+3*15)-4=29 | | 6-3(2x-9)= | | 3(3+3y)-4=29 | | 48-x^2=12 | | 4g+7-6+5g=64 | | -15=-3(n+7) | | -2(x+7)= | | 36x^3+27x^2-18x-9= | | 10x+3=4(2x+1)-x+7 | | 9x-3(2x+2)=15 | | 2x+7=x-1 |

Equations solver categories